The analysis of Lactobacillus spp. distribution in the vaginal microbiota of Polish women with abnormal Pap smear result - Frąszczak, Karolina; Barczyński, Bartłomiej; Siwiec, Radosław; Kondracka, Adrianna; Malm, Anna; Kotarski, Jan; Witt, Elzbieta; Korona-Głowniak, Izabela (Frontiers in Microbiology, 2023)
Introduction A healthy vaginal microbiota is represented mainly by Lactobacillus spp. and plays a vital role in maintaining the functional balance in the vaginal environment. Scientists have drawn attention to possible correlations between the vaginal microbiome and gynecological neoplasms. Several recent studies have shown a potential link between the vaginal microbiome and the risk of developing cervical cancer from human papillomavirus (HPV) infection. This study aimed to compare the prevalence and abundance of various lactic acid bacteria species (LABs) in vaginal swabs from healthy controls and patients with abnormal Pap smear results. Methods The study included 100 women (79 patients with abnormal cervical Pap smear results and 21 controls) from whom vaginal swabs were collected. Real-time quantitative PCR was used to determine seven lactic acid bacteria (LAB) species and their quantities. Results Most patients were colonized by two Lactobacillus species, primarily L. gasseri (93%) and L. crispatus (83%). Patient age and place of residence were associated with the diversity of LAB in the vaginal microbiota. The abundance of L. delbrueckii in the vaginal microbiota increased, whereas the abundance of L. gasseri abundance decreased, with patient age. L. acidophilus and Limosilactobacillus fermentum were significantly more often detected in patients living in rural versus urban areas. Statistical analysis did not show any significant differences in LAB between groups of patients with various changes on smear tests. Discussion The degree of dysplastic changes in the endothelium or the presence of a group of atypical cervical stratified epithelial cells was not associated with significant changes in the studied vaginal bacteria.